Aplikasi Perhitungan Harga Pokok Produksi Pada PT.X Menggunakan Metode Job Order Costing - Lois Christian; Silvia Rostianingsih; Rudy Adipranata (Jurnal Infra, 2016)
PT.X is a company engaged in the manufacturing of bread. At the time of this recording and bookkeeping at PT.X still uses a manual system, the manual bookkeeping system often makes companies become difficult to oversee and regulate the accounting system in the company. Calculation of Cost of Production is still done manually by the company to make an estimate of production cost. The calculations were done manually because the company's difficulties in calculating gains and losses that are definitely in the production process and affect the profits and losses earned by the company.Based on this background, it designed a system of calculation of production cost which automatically so that helps the enterprise system in the future. Application design process is done in several stages, with the initial stages of surveying field conditions that exist within the company and then designing the Data Flow Diagram and Entity Relationship Diagram before making an application. For the making of the application uses Microsoft Access 2013 as data storage and programming language using Microsoft Visual Studio 2012. In the calculation of production cost using Job Order Costing method that can be updated automatically.The results obtained from the application that has been made, among others, the application of calculating the cost of production accurately, applications make the process of buying and selling, the application generates a report production process accurately and precisely at any time when needed and application to surf the flow of costs in the production process. From the results of application testing 80% of users assume that the assessment of the overall program is very good, while 20% of other users assume that a good assessment of the overall program.